PENGEMBANGAN BAHAN AJAR MEMBACA PEMAHAMAN BERDASARKAN STRATEGI PLAN (PREDICT, LOCATE, ADD, NOTE) UNTUK SISWA KELAS VII - Sudiati Sudiati; Nurhidayah Nurhidayah (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to produce reading comprehension learning materials based on the PLAN strategy and to find out the appropriateness for Grade VII students. This was adesign and development study. The stages were taken from those of Borg and Gall. Thedata were qualitative and quantitative in nature. The data trustworthiness was assessedin terms of credibility, transferability, dependability, and confirmability. The researchinstruments were an interview guide and a questionnaire. The data were analyzed bythe qualitative technique and descriptive statistics. The research product is a readingcomprehension course book consisting of an introduction, contents, and a supplement.The results of the evaluation by the the materials expert and the learning expert showthat the developed course book is good in terms of content appropriateness, presentation,language, and graphics. These are indicated by a mean score of 3.78 from the the materialsexperts and 3.80 from the the learning expert.Keywords:learning materials, reading comprehension, PLAN strategy